Uso isolado e combinado de bisfosfonatos, estatina e flavonóide em ratas osteoporóticas - Amaral, Gláucia Guimarães; Del Carlo, Ricardo Junqueira; De Oliveira, Tânia Toledo; Louzada, Mário Jefferson Quirino [UNESP]; Valadares, Rilene Ferreira Diniz; Ribeiro, Mariella Dias; Da Pinto, Aloísio Silva (My University, 2014)
This study aimed to treat osteoporosis induced by ovariectomy through the single and combined use, by employing, in this case, half of the defined doses of the isolated compounds etidronate, risedronate (bisphosphonates), pravastatin (statin) and ipriflavone (flavonoid).The experiment consisted of 66 rats were divided into 11 groups of 6 animals, taking control and osteoporosis, the most isolated groups etidronate, risedronate, pravastatin and ipriflavone and associated etidronate + pravastatin, etidronate + ipriflavone, risedronate + pravastatin, risedronate + ipriflavone and pravastatin + ipriflavone. After 12 weeks of ovariectomy, began administering the drug orally for 30 days. After 35 days, the animals were sacrificed and blood was collected for biochemical analysis and the tibias for analysis bone mineral density.The value of the biochemical markers calcium, phosphorus, albumin, total protein and bone alkaline phosphatase presented no statistically significant differences. These results provide no information for the diagnosis and monitoring of osteoporosis. Bone densitometry presented significant results for induction and for different treatments, in relation to the osteoporotic group. The results reveal that associations have the same pharmacological activity as isolated substances, and no antagonistic effect was observed. Thus, associations can be a therapeutic alternative, since possible side effects can be reduced by the administration of half the individual dose prescribed.
Isolated and combined use of bisphosphonates, statins and flavonoids in osteoporotic female rat
Keywords: Bisphosphonates; Osteoporosis; Ovariectomy; Statins and flavonoids